An empirical investigation on the influence of online reviews affects the individual’s purchase intention in Malaysia - Ong, Wei Chi (2022)
In the rapidly growing Internet of Malaysia, online shopping has spread to the daily lives of most people. When making purchases on the Internet platform, consumers must carefully analyse the product’s characteristic, price, quality information, and other and carefully select them to increase the satisfaction of shopping. Online product reviews are one of the sources of product feature information that online buyers are increasingly valuing. This research will examine the literature on online reviews and the influencing review factors primarily focused on Uses and Gratification Theory (UGT) and StimulusResponse Model. Therefore, this paper aims to investigate the influence of perceived information quality, information quantity, review credibility and review valence on Malaysian consumers’ purchase intention when online shopping. With this aim, this research used Package for the Social Sciences (SPSS) version 26 .0 Statistical to test the proposed hypothesis with a valid sample of 391 respondents. The target respondents for this study are the Malaysian who have purchased products through online. Q questionnaires for this research were distributed conveniently in Malaysia through convenience sampling method. The findings of this study revealed that perceived information quality, information quantity, review credibility and review valence have a positive relationship on purchase intention in Malaysia. Review valence has the strongest influences towards consumers’ purchase intention. This study defines constructs for purchase intention after reading online consumer reviews towards a product, which serves as a good framework for practitioners consumers and set to design business strategies to retain as a foundation for future research studies. There are some limitation s faced throughout the process of conducting this research project, and thus some recommendations are presented to propose beneficial suggestion and call for future studies.